Life Cycle Saving and Dissaving Revisited across Three-Tiered Income Groups: Starting Hypotheses, Refinement through Literature Review, and Ideas for Empirical Testing - Robert Holzmann; Mercedes Ayuso; Estefanía Alaminos; Jorge Miguel Bravo (Institute of Labor Economics (IZA), 2019)
The lifecycle approach is the workhorse to model saving decisions of individuals. It conjectures individuals preferring a constant consumption stream across their lifecycle saving till retirement and dis-saving thereafter. The reality is often at odd with this assumption giving rise to our conjectured three-tier life-cycle model by income groups. The low-income tier does little saving and in consequence little dissaving; the high-income tier does save during active life and profits often from bequests, but no dissaving is taking place unless hit by a major shock; only the middle tier behaves broadly as predicted. The drivers for such a differentiated behavior are conjectured to be threefold: External settings such as a multitude of shocks; preferences deviations such a behavioral bias, and institutional settings and interventions, such as minimum income provisions. The paper outlines these corresponding hypotheses, presents some first conceptual and empirical support, and reviews the international literature on the conjectured drivers. The review of international literature does not shatter our conjecture of a broadly three-tiered and reframed applicability of the life cycle model but offers some first precisions and wrinkles. The paper proposes next conceptual and empirical steps, including enriching existing wealth distribution estimates at retirement with sound estimates of social insurance wealth (pension and health), focused hypothesis testing of the key drivers with household panel data, and formulating policy responses if the new hypotheses are not rejected.
Keywords: D15; D31; E21; 330; shocks and saving/dissaving; wealth distribution; financial wealth; property; social security wealth